Etika Profesi Konselor: Analisis Filsafat Moral Dalam Praktik Bimbingan Dan Konseling - Darni; Prasetya, Akhmad Fajar (Jurnal Ilmu Bimbingan dan Konseling, 2025)
Professional ethics play a vital role in the implementation of Guidance and Counseling (BK) services because they relate directly to the counselor's moral responsibility toward the counselee. Counseling services, built through intense interpersonal relationships, require counselors not only to obey the code of ethics normatively but also to possess reflective ethical awareness. This article aims to analyze the professional ethics of counselors from a moral philosophy perspective as a normative basis for ethical decision-making. This research employs a qualitative approach with a conceptual-philosophical design through a literature review of moral philosophy theories, counselor professional code of ethics documents, and scientific publications in the field of Guidance and Counseling. Data were analyzed descriptively and reflectively by placing the counselor's professional ethics within the frameworks of deontological, teleological, and virtue ethics. The results show that the principles of counselor professional ethics are based on universal moral values, such as respect for human dignity, responsibility, justice, and care. These three philosophical approaches complement each other in building a comprehensive understanding of professional ethics—one that is oriented not only toward rule compliance but also toward moral objectives and the formation of the counselor's character. The conclusion of this study emphasizes that a philosophical understanding of professional ethics is essential to strengthen moral integrity and the quality of humanistic and dignified counseling practices.